A Survey of Active Galaxies at TeV Photon Energies with the HAWC Gamma-Ray Observatory - Albert, A.; Alvarez, C.; Camacho, J. R. Angeles; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A. Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) Gamma-Ray Observatory continuously detects TeV photons and particles within its large field of view, accumulating every day a deeper exposure of two-thirds of the sky. We analyzed 1523 days of HAWC live data acquired over four and a half years, in a follow-up analysis of 138 nearby (z < 0.3) active galactic nuclei from the Third Catalog of Hard Fermi-LAT sources culminating within 40 degrees of the zenith at Sierra Negra, the HAWC site. This search for persistent TeV emission used a maximum-likelihood analysis assuming intrinsic power-law spectra attenuated by pair production of gamma-ray photons with the extragalactic background light. HAWC clearly detects persistent emission from Mkn 421 and Mkn 501, the two brightest blazars in the TeV sky, at 65 sigma and 17 sigma level, respectively. Marginal evidence, just above the 3 sigma level, was found for three other known very high-energy emitters: the radio galaxy M87 and the BL Lac objects VER J0521+211 and 1ES 1215+303, the latter two at z similar to 0.1. We find a 4.2 sigma evidence for collective emission from the set of 30 previously reported very high-energy sources, with Mkn 421 and Mkn 501 excluded. Upper limits are presented for the sample under the power-law assumption and in the predefined (0.5-2.0), (2.0-8.0), and (8.0-32.0) TeV energy intervals.
CRIS-Team WoS Importer:2021-03-05